2018
DOI: 10.1007/s11676-018-0715-5
|View full text |Cite
|
Sign up to set email alerts
|

Litter decomposition and the degradation of recalcitrant components in Pinus massoniana plantations with various canopy densities

Abstract: To understand the decomposition characteristics of Pinus massoniana foliar litter and the degradation of its refractory compounds in plantations under five canopy densities, a litter bag experiment over a decomposition time of 392 days was carried out. The results show that canopy density significantly affected decomposition rates of litter and degradation rate of lignin and cellulose. Litter decomposition rates decreased significantly with decreasing canopy density. Both lignin and cellulose degradation rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
12
1
Order By: Relevance
“…The presence of large fauna has a recognized impact on decomposition in terrestrial ecosystems around the world (a review in HANDA et al, 2014). While soil fauna has an important role to organic material decomposition in the rainforest, influencing N and C cycles (e.g., YANG; CHEN, 2009), and it is the main driver on Pinus massoniana litter decomposition and breakdown of its refractory compounds (ZHANG et al, 2019), our field experiment using litter bags showed no significant differences in litter mass loss when macrofauna and most of the mesofauna were excluded.…”
Section: Litter Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of large fauna has a recognized impact on decomposition in terrestrial ecosystems around the world (a review in HANDA et al, 2014). While soil fauna has an important role to organic material decomposition in the rainforest, influencing N and C cycles (e.g., YANG; CHEN, 2009), and it is the main driver on Pinus massoniana litter decomposition and breakdown of its refractory compounds (ZHANG et al, 2019), our field experiment using litter bags showed no significant differences in litter mass loss when macrofauna and most of the mesofauna were excluded.…”
Section: Litter Decompositionmentioning
confidence: 99%
“…Pine species including P. taeda are recognized as low quality showing slow decomposition rates, which depends on climatic conditions and its effects on microbial growth rate (OLSSON et al, 2019). Higher decay in litter reminiscent material at the beginning of the process can be related to the decomposition of water-soluble compounds and some labile organic components, while the lower decay in late stages is related to recalcitrant components (ZHANG et al, 2019). Needles of coniferous species contain more recalcitrant compounds such as cellulose, hemicelluloses, lignin, and tannins when compared with broad-leaved tree species (GUO et al, 2009), besides needles being a hard material to be breakdown by soil faunal groups, which justify the main role of microorganisms, especially fungi (PURAHONG et al, 2014), in this process.…”
Section: Litter Decompositionmentioning
confidence: 99%
“…In addition, canopy coverage can influence soil moisture conditions through rainfall interception or by decreasing the rate of evaporation from the soil through decreased sunlight (Prescott, 2002). Previous studies have shown that canopy structure is an important indirect driver of decomposition in regional and large-scale analyses (Joly et al, 2017;Wallace et al, 2018;Zhang et al, 2019). However, the overall contribution of stand structure and organic matter input can be masked by considering only their direct effects on litter decomposition (Wallace et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term impact of litter can modify nutrient cycling differently from native species(Veeraragavan et al 2018). Besides that, the soil moisture is lowest in invaded environment (Afreen and Singh 2019), and this can be explained by litter hydrophobic trait(Zhang et al 2019…”
mentioning
confidence: 99%